Handsome Ransom Jackson : accidental Big Leaguer - Jackson, Ransom, 1926-2019 (Rowman and Littlefield, 2016)
"Handsome Ransom" Jackson was an all-star third baseman in the 1950s. He was in Chicago in 1953 when Ernie Banks became the first African American to play for the Cubs. He was in Brooklyn in 1956, the year Jackie Robinson retired and Don Larsen of the New York Yankees threw a perfect game in the World Series. In 1957, Jackson was the last Brooklyn player to hit a home run before the team was moved to L.A. This autobiographical account, told by Ransom Jackson Jr. to Gaylon H. White, shares all these stories and more, spanning from Jackson's youth to his college years playing both football and b